Measurement of serum 7α‐hydroxy‐4‐cholesten‐3‐one as a marker of bile acid malabsorption in dogs with chronic diarrhoea: a pilot study. Issue 1 (6th April 2016) - Kent, A. C. C.; Cross, G.; Taylor, D. R.; Sherwood, R. A.; Watson, P. J.
Abstract : Bile acid malabsorption is a common cause of chronic diarrhoea in people, however it has never previously been investigated in dogs, despite clinical suspicion of its existence. The goal of this study was to assess the feasibility of measuring serum 7α‐hydroxy‐4‐cholesten‐3‐one (C4) in dogs, as a potential marker of bile acid malabsorption, and to see whether this is related to clinical disease severity or the presence of hypocobalaminaemia. Serum C4 concentration was measured in 20 clinically healthy control dogs and 17 dogs with chronic diarrhoea. Three of the 17 affected dogs (17.6 per cent) had a C4 concentration significantly above the range of clinically healthy dogs; these dogs were all poorly responsive to conventional therapy. These results suggest that bile acid malabsorption may be a clinically relevant disorder in dogs with chronic diarrhoea and serum C4 may be a useful tool to investigate this further.